Efficacy and Scope of Biochemic Remedies in Homoeopathy (Homoeopathy for All, 2025)
Dr. Wilhelm Heinrich Schuessler  introduced the Biochemic system of  medicine or tissue remedies which  are homoeopathically prepared  from mineral salts. Biochemic  medicines have an effect at the  physiological level. The World  Health Organization defines this  biochemical medicine method as  inorganic cellular salt therapy. It is  one of the complementary therapies  introduced as a tissue salt remedy.  These nutrients help regulate cellular  functions and support health by  regulating cellular salt levels. These  tissue remedies are made by adding  a minimal amount of tissue salt.  The biochemical tissue remedies  are inorganic tissue salts. There are  a total of twelve biochemic tissue  remedies which have their own  individual properties.
Keywords: Homoeopathy; Tissue salt; alternative medicine; Treatment; Healing